Artificial ascites for organs at risk sparing in intrapelvic brachytherapy: a case report of recurrent uterine cervical carcinoma adjacent to the bowel - Murakami, Naoya (BJR Case Rep, 2018)
Artificial ascites has been reported as an effective technique to reduce the risk of thermal injury in radiofrequency ablation of liver tumors by increasing the distance of collateral organs located next to the ablated sites. In this case report we share our experience with artificial ascites in an attempt to reduce the toxicity of collateral adjacent organs in the setting of re-irradiation for recurrent cervical cancer. A 52-year-old female who developed local recurrence after definitive radiation therapy was treated with interstitial re-irradiation by means of image-guided, (single-implant/multi fraction) high-dose-rate brachytherapy. Because the sigmoid colon was in close proximity to the recurrent tumor lesion, artificial ascites was generated before each treatment fraction by percutaneous injection of a defined amount of saline solution through the abdominal wall to create additional space between the two volumes. Artificial ascites showed a dosimetric improvement by reducing the sigmoid colon D(0.1cc) per fraction from 286 cGy before to 189 cGy after saline injection. No severe complication was associated with the injection procedure.